The importance of supervisor support for the work outcomes and psychological well-being of Malaysian low-income working mothers - Zulkifli, Syara Shazanna; Hamzah, Hazalizah (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
Low-income working mothers are susceptible to well-being issues. However, research on the interplay between supervisor support and the work outcomes and psychological well-being of Malaysian low-income working mothers is scarce. Therefore, this study identifies the relationship between work outcomes (work stress, work-life balance, workplace bullying) and the moderating role of supervisor support in the psychological well-being of working mothers. Using purposive sampling, data were obtained from a survey of 269 respondents (M-age = 38.15, SD-age = 8.14) employing offline and online methods. The participants completed the demographic section, Psychological Well-being Scale, Work Stress Scale, Work-life Balance Checklist, Malaysian Workplace Bullying Index, and Supervisor Support Scale. Structural equation modelling analysis showed that work stress was the main contributor to psychological well-being (β = -0.41, t = -2.87, p = .004), followed by supervisor support (β = 0.29, t = 3.34, p <.001), and workplace bullying (β = -0.23, p = .048). In addition, supervisor support significantly weakened the impact of work stress on psychological well-being (β = -0.14, t = -2.00, p = .045). The study concludes that supervisor support enhances psychological well-being and reduces the negative burden of work stress on the psychological well-being of Malaysian low-income working mothers. Identifying the most significant contributors to psychological well-being can help working mothers to become more aware of the negative side effects of work, and encourage them to find effective solutions to maintain their psychological well-being. Finally, the study emphasizes for supervisors and human resource personnel the importance of supervisory roles in improving the work environment and providing strengthened support for psychological well-being.